Composition and film material transfer method

By using the adhesion film formed by the polypropylene carbonate and polyvinyl alcohol composition, the problem of poor electrode bonding effect in the traditional transfer method is solved, and high-precision electrode transfer and performance improvement in optoelectronic devices is achieved.

CN119286320AActive Publication Date: 2025-01-10SONGSHAN LAKE MATERIALS LAB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310839592.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10
Estimated Expiration
2043-07-10

AI Technical Summary

Technical Problem

In optoelectronic devices, the adhesion film used in the conventional transfer method results in poor bonding between the patterned electrode and the target substrate, and the direct photolithography method for preparing the electrode on semiconductor materials may lead to performance attenuation.

Method used

Provided is a composition comprising 1 part to 20 parts of polypropylene carbonate and 1 part to 2 parts of polyvinyl alcohol for forming an adhesive film, by forming a thin film material on the surface of the substrate, covering the adhesive film, and separating it. And it is attached to the target substrate, and the adhesion film is removed, the temperature and cleaning process are controlled to achieve a good fit.

Benefits of technology

A good bonding effect between the patterned electrode and the target substrate is achieved, the transfer accuracy and performance of the electrode are improved, and the performance attenuation caused by the direct preparation of the electrode on the semiconductor material is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286320A_ABST
    Figure CN119286320A_ABST
Patent Text Reader

Abstract

The invention relates to a composition and a thin film material transfer method. The composition provided by the invention is prepared from the following components in parts by mass: 1 to 20 parts of polypropylene carbonate and 1 to 2 parts of polyvinyl alcohol. The composition is prepared from the following components in parts by mass: 1 to 20 parts of polypropylene carbonate and 1 to 2 parts of polyvinyl alcohol. Within the range of the mass fraction of the polypropylene carbonate and the mass fraction of the polyvinyl alcohol, an adhesive film comprising the composition has good mechanical strength and high surface viscosity in an amorphous state, and the composition can be applied to transfer of patterned electrodes. When the composition is used for transferring the patterned electrode, the patterned electrode can be well grabbed and released, and a good attaching effect between the patterned electrode and a target substrate can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of material transfer, and in particular to a composition and a thin film material transfer method. Background Art

[0002] Patterned electrodes are one of the basic components of optoelectronic devices. Their preparation process, optoelectronic properties, contact quality, patterning accuracy, etc. may affect the basic performance and integration of the device. At present, in optoelectronic devices, the electrode construction methods mainly include the following: photolithography, mask evaporation, printing and transfer. Compared with mask evaporation and printing, photolithography has the advantage of high precision. However, the process of photolithography involves process flows such as exposure, development, and etching, which usually require the introduction of conditions such as heating and strong alkaline solvents. It is difficult to directly process on some common polymer flexible substrates, and in the process of preparing semiconductor devices, directly using photolithography to prepare patterned electrodes on semiconductor materials may cause the performance of semiconductor materials to decay. The transfer method can transfer patterned electrodes from other substrates to the target substrate, avoiding the preparation of patterned electrodes directly on the semiconductor material. However, when the adhesive film used in the traditional transfer method is used to transfer the patterned electrode, the bonding effect between the patterned electrode and the target substrate is poor. Summary of the invention

[0003] Based on this, it is necessary to provide a composition and a thin film material transfer method. The composition can be applied to the transfer of patterned electrodes, and when the patterned electrodes are transferred using the composition, a better bonding effect between the patterned electrodes and the target substrate can be achieved.

[0004] In a first aspect, the present application provides a composition comprising the following components in parts by weight:

[0005] 1 to 20 parts of polypropylene carbonate and 1 to 2 parts of polyvinyl alcohol.

[0006] In some embodiments, the composition has a glass transition temperature of 35°C to 45°C.

[0007] In a second aspect, the present application provides a thin film material transfer method, comprising: forming a thin film material on a surface of a substrate;

[0008] forming an adhesive film on the film material, wherein the adhesive film comprises any one of the above-mentioned compositions, so that the adhesive film covers the film material to obtain a composite film comprising the film material and the adhesive film;

[0009] Separating the composite film from the substrate, and attaching the composite film to a target substrate so that the thin film material of the composite film is in contact with the target substrate;

[0010] The adhesive film is removed.

[0011] In some embodiments, during the process of separating the composite film from the substrate, the temperature of the adhesive film is controlled to be 25° C. to 50° C.

[0012] In some embodiments, laminating the composite film to a target substrate comprises:

[0013] Heating causes the composite film to conform to the target substrate.

[0014] In some embodiments, during the heating process to make the composite film adhere to the target substrate, the heating temperature is controlled to be 50° C. to 150° C.

[0015] In some embodiments, removing the adhesive film comprises the following steps:

[0016] The adhesive film is cleaned using one or more of acetone, chloroform, ethanol and isopropyl alcohol.

[0017] In some embodiments, forming a thin film material on a surface of a substrate comprises the following steps:

[0018] reducing the surface energy of the substrate;

[0019] The thin film material is prepared on the surface of the substrate after the surface energy is reduced.

[0020] In some embodiments, forming an adhesive film on a thin film material comprises the following steps:

[0021] preparing a mixed solution of polypropylene carbonate and polyvinyl alcohol;

[0022] The mixed solution is transferred onto the surface of the thin film material and dried.

[0023] In some embodiments, the thin film material includes one or more of a metal electrode, a polymer electrode, a metal grid, and a two-dimensional material.

[0024] In some embodiments, the material of the substrate includes at least one of glass, quartz, silicon wafer, ceramic, metal and plastic.

[0025] In some embodiments, the material of the target substrate includes at least one of glass, quartz, silicon wafer, ceramic, metal and plastic.

[0026] The composition comprises 1 to 20 parts by weight of polypropylene carbonate and 1 to 2 parts by weight of polyvinyl alcohol. Within the range of the weight of the polypropylene carbonate and the weight of the polyvinyl alcohol, the adhesive film comprising the composition has good mechanical strength and strong surface viscosity in an amorphous state. The composition can be applied to the transfer of patterned electrodes, and when the patterned electrodes are transferred using the composition, the patterned electrodes can be better grasped and released, and a better bonding effect between the patterned electrodes and the target substrate can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] FIG1 is a schematic diagram of a thin film material transfer method according to an embodiment of the present application;

[0028] FIG2 is a schematic diagram of transferring a thin film material on a curved surface according to an embodiment of the present application;

[0029] FIG3 is a schematic diagram of patterned gold electrode transfer provided in Example 1 of the present application, wherein (a) is a physical picture of the patterned gold electrode after being transferred to the target substrate, (b) is an optical microscope picture of the patterned gold electrode after being transferred to the target substrate, and (c) is a physical picture of the patterned gold electrode after being peeled off from the substrate through an adhesive film and transferred to a glass bottle body;

[0030] FIG4 is a scanning electron microscope image of the patterned silver electrode provided in Example 2 of the present application after being transferred to an irregular curved target substrate, wherein (a) is a scanning electron microscope image of a strip electrode after being transferred to an irregular curved target substrate, and (b) is a scanning electron microscope image of a point electrode after being transferred to an irregular curved target substrate;

[0031] FIG5 is a physical picture of the transferred patterned polymer electrode provided in Example 3 of the present application, wherein (a) is a physical picture of the patterned polymer electrode transferred to a 2-inch silicon dioxide substrate, (b) is an optical microscope picture of the patterned polymer electrode transferred to a target substrate, and (c) is a physical picture of the patterned polymer electrode after being transferred to a flexible substrate;

[0032] FIG6 is a scanning electron microscope image of the transferred patterned silver nanowire grid electrode provided in Example 4 of the present application, wherein (a) is a patterned silver nanowire grid electrode transferred to an irregular bionic skin surface, and (b) is a partial enlarged view of (a);

[0033] FIG. 7 is a schematic diagram of the process of directional transfer of patterned gold electrodes provided in Example 5 of the present application;

[0034] FIG8 is a schematic diagram comparing the field effect transistor provided in Example 5 of the present application and the field effect transistor with a conventional vapor deposition electrode, wherein (a) is a schematic diagram of the structure of the field effect transistor, (b) is an optical microscope image of the transistor of the transfer electrode and the vapor deposition electrode, (c) to (d) are performance curves of the field effect transistor prepared in Example 5, and (e) to (f) are performance curves of the field effect transistor with a conventional thermal vapor deposition electrode;

[0035] FIG9 is a flexible field effect transistor provided in Example 6 of the present application, wherein (a) is an optical microscope image of the flexible field effect transistor, and (b) is an electrical performance characterization image;

[0036] FIG10 is a graph showing the electrical performance test of a large-area field effect transistor array provided in Example 7 of the present application, wherein (a) to (c) are graphs showing the mobility test results of 81 devices; (d) to (f) are graphs showing the switch ratio test results of 81 devices;

[0037] FIG11 is an optical microscope image of the patterned gold electrodes after transfer provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present application;

[0038] 12 is a thermal analysis comparison diagram of polypropylene carbonate, polypropylene carbonate-polyvinyl alcohol mixed film and polyvinyl alcohol provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0039] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0041] An embodiment of the present application provides a composition, comprising the following components in parts by weight: 1 to 20 parts of polypropylene carbonate and 1 to 2 parts of polyvinyl alcohol.

[0042] The composition comprises 1 to 20 parts by weight of polypropylene carbonate and 1 to 2 parts by weight of polyvinyl alcohol. Within the range of the weight of the polypropylene carbonate and the weight of the polyvinyl alcohol, the adhesive film comprising the composition has good mechanical strength and strong surface viscosity in an amorphous state. The composition can be applied to the transfer of patterned electrodes, and when the patterned electrodes are transferred using the composition, the patterned electrodes can be better grasped and released, and a better bonding effect between the patterned electrodes and the target substrate can be achieved.

[0043] Optionally, the mass fraction of polypropylene carbonate is 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.

[0044] Optionally, the mass fraction of polyvinyl alcohol is 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2 parts.

[0045] In some embodiments, the glass transition temperature of the composition is 35° C. to 45° C. Alternatively, the glass transition temperature of the composition is 35° C., 36° C., 37° C., 38° C., 39° C., 40° C., 41° C., 42° C., 43° C., 44° C., or 45° C.

[0046] In some embodiments, the composition is composed of the following components in parts by weight: 1 to 20 parts of polypropylene carbonate and 1 to 2 parts of polyvinyl alcohol.

[0047] Referring to Figure 1, another embodiment of the present application provides a method for transferring a thin film material, including: forming a thin film material on the surface of a substrate; forming an adhesive film on the thin film material, the adhesive film including any of the above compositions, so that the adhesive film covers the thin film material to obtain a composite film including the thin film material and the adhesive film; separating the composite film from the substrate, and attaching the composite film to a target substrate so that the thin film material of the composite film is in contact with the target substrate; and removing the adhesive film.

[0048] In the above-mentioned film material transfer method, an adhesive film is used to transfer the film material, and the adhesive film includes any of the above-mentioned compositions, that is, the adhesive film includes 1 to 20 parts by mass of polypropylene carbonate and 1 to 2 parts of polyvinyl alcohol. The glass transition temperature of polypropylene carbonate is low, but its fluidity is strong, and the glass transition temperature of polyvinyl alcohol is high, but it has almost no fluidity. Within the mass fraction of the polypropylene carbonate and the mass fraction of the polyvinyl alcohol, the adhesive film has both a low glass transition temperature and moderate fluidity at a certain temperature. The adhesive film also has good mechanical strength and strong surface viscosity in an amorphous state, and the adhesive film is easier to remove by an organic solvent. The use of the adhesive film can better grasp and release the film material to be transferred, and when the patterned electrode is transferred, a better bonding effect between the patterned electrode and the target substrate can be achieved.

[0049] In some embodiments, the method of forming the adhesive film on the surface of the substrate includes one of spin coating, spray coating, and blade coating.

[0050] 2 , in the thin film material transfer method, the adhesive film also has a relatively low Young's modulus, and is also applicable to transferring thin film materials on irregular curved surfaces.

[0051] In some embodiments, the adhesive film is a mixed film of 1 to 20 parts by weight of polypropylene carbonate and 1 to 2 parts by weight of polyvinyl alcohol.

[0052] In some embodiments, during the separation of the composite film and the substrate, the temperature of the adhesive film is controlled to be 25°C to 50°C. At this temperature, the adhesive film has good adhesion to the film material and can grab the film material. Optionally, during the separation of the composite film and the substrate, the temperature of the adhesive film is controlled to be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C.

[0053] In some embodiments, laminating the composite film to the target substrate includes: applying heat to cause the composite film to be laminar to the target substrate.

[0054] In some embodiments, during the heating process so that the composite film is attached to the target substrate, the heating temperature is controlled to be 50°C to 150°C. Within this temperature range, the fluidity of the adhesive film can be increased, and the film material can be further attached to the target substrate. Optionally, during the heating process so that the adhesive film-film material composite film is further attached to the target substrate, the temperature of the adhesive film is controlled to be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C.

[0055] In some embodiments, removing the adhesive film comprises the following step: cleaning the adhesive film using one or more of acetone, chloroform, ethanol and isopropyl alcohol.

[0056] In some embodiments, forming an adhesive film on the thin film material comprises the following steps: preparing a mixed solution of polypropylene carbonate and polyvinyl alcohol; transferring the mixed solution to the surface of the thin film material and drying it.

[0057] In some embodiments, preparing a mixed solution of polypropylene carbonate and polyvinyl alcohol comprises the following steps:

[0058] In some embodiments, preparing a mixed solution of polypropylene carbonate and polyvinyl alcohol comprises the following steps:

[0059] A polypropylene carbonate solution and a polyvinyl alcohol solution are separately prepared and mixed to obtain a mixed solution.

[0060] In some embodiments, the mass concentration of polypropylene carbonate in the polypropylene carbonate solution is 10% to 35%. Optionally, the mass concentration of polypropylene carbonate in the polypropylene carbonate solution is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%.

[0061] In some embodiments, the mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5% to 20%. Optionally, the mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0062] In some embodiments, the method for preparing a thin film material includes: reducing the surface energy of a substrate; and preparing the thin film material on the substrate after the surface energy is reduced. Preparing the thin film material on the substrate after the surface energy is reduced can reduce the adhesion between the thin film material and the substrate, making it easier to peel off the thin film material.

[0063] In some embodiments, reducing the surface energy of the substrate includes: performing plasma cleaning on the surface of the substrate, performing hydroxylation treatment on the surface after plasma cleaning, and performing monomolecular layer modification on the treated surface.

[0064] In some embodiments, the method for preparing the thin film material includes one or more of mask evaporation, printing, dry etching, tape stripping, wet etching, screen printing and photolithography.

[0065] In some embodiments, the thin film material includes one or more of a metal electrode, a polymer electrode, a metal grid, and a two-dimensional material. It is understood that the above thin film materials can be patterned or non-patterned thin films.

[0066] In some embodiments, the material of the substrate includes at least one of glass, quartz, silicon wafer, ceramic, metal, and plastic.

[0067] The material of the target substrate includes at least one of glass, quartz, silicon wafer, ceramic, metal and plastic.

[0068] In some embodiments, the thin film material transfer method comprises the following steps:

[0069] (1) Providing a substrate, and performing plasma cleaning on a surface of the substrate to reduce the surface energy of the substrate.

[0070] (2) Preparing a thin film material on the surface of a substrate after reducing the surface energy.

[0071] (3) forming an adhesive film on the film material so that the adhesive film covers the film material, wherein the adhesive film comprises 1 to 20 parts by weight of polypropylene carbonate and 1 to 2 parts by weight of polyvinyl alcohol, thereby obtaining a composite film comprising the film material and the adhesive film.

[0072] (4) Controlling the temperature of the adhesive film to 25°C to 50°C, separating the composite film from the substrate, and attaching the composite film to the target substrate so that the thin film material of the composite film contacts the target substrate.

[0073] (5) The temperature of the adhesive film is controlled to be 50°C~150°C so that the film material can be further bonded to the target substrate.

[0074] (6) The adhered film is cleaned using one or more of acetone, chloroform, ethanol and isopropanol to remove the adhered film.

[0075] In some embodiments, the thin film material transfer method comprises the following steps:

[0076] (1) Providing a substrate, and performing plasma cleaning and monomolecular layer modification on the surface of the substrate to reduce the surface energy of the substrate.

[0077] (2) Preparing a thin film material on the surface of a substrate after reducing the surface energy.

[0078] (3) forming an adhesive film on the film material so that the adhesive film covers the film material, wherein the adhesive film comprises 1 to 20 parts by weight of polypropylene carbonate and 1 to 2 parts by weight of polyvinyl alcohol, thereby obtaining a composite film comprising the film material and the adhesive film.

[0079] (4) Controlling the temperature of the adhesive film to 25°C to 50°C, separating the composite film from the substrate, and attaching the composite film to the target substrate so that the thin film material of the composite film contacts the target substrate.

[0080] (5) The temperature of the adhesive film is controlled to be 50°C~150°C so that the film material can be further bonded to the target substrate.

[0081] (6) The adhered film is cleaned using one or more of acetone, chloroform, ethanol and isopropanol to remove the adhered film.

[0082] The following are specific embodiments

[0083] Example 1

[0084] A method for transferring a patterned gold electrode, the specific steps are as follows:

[0085] (1) The silicon substrate is ultrasonically cleaned with deionized water, isopropanol, and acetone in sequence, and the cleaned silicon substrate is dried. The surface of the silicon substrate is cleaned by plasma to hydroxylate the surface, and a monolayer of octadecyltrichlorosilane is modified on the silicon substrate by a vapor phase method. 20 μL~80 μL of octadecyltrichlorosilane is placed in a culture dish, and the silicon substrate to be modified is located directly above the culture dish containing octadecyltrichlorosilane. The culture dish and the silicon substrate to be modified are placed in a vacuum drying oven and maintained in a vacuum state for 10 min~30 min. The drying oven temperature is 60℃~90℃. After cooling to room temperature, the substrate is immersed in chloroform and ultrasonically cleaned for 3 min~10 min. Then, the silicon substrate is placed in a drying oven at 100℃~130℃ for heating and drying. This step can adjust the surface energy of the substrate and reduce the adhesion between the substrate and the patterned gold electrode.

[0086] (2) The conventional photolithography method is used to prepare a patterned gold electrode, which specifically includes the following steps: Spin-coat the surface of the silicon substrate obtained in step (1) with a photoresist (AZ 5214 E) at a rotation speed of 3000 rpm to 6000 rpm for 40 s to 60 s, and then heat the solid film at 100°C to 120°C for 60 s to 600 s. Place the photoresist under a photolithography mask for ultraviolet exposure, and then place the substrate in a developer AZ 300MIF for 60 s to 200 s. After taking out the substrate, wash the substrate with deionized water, blow dry with nitrogen, and place the patterned photoresist in a thermal evaporator to evaporate the gold electrode. Wash away the residual photoresist with acetone to obtain a patterned gold electrode.

[0087] (3) Prepare a polypropylene carbonate solution and a polyvinyl alcohol solution respectively, wherein the solvent of the polypropylene carbonate solution is anisole, the mass concentration of polypropylene carbonate is 10%~35%, and the solvent of the polyvinyl alcohol solution is deionized water, and the mass concentration of polyvinyl alcohol is 5%~20%. Mix the prepared polypropylene carbonate solution and polyvinyl alcohol solution in a mass ratio of (1~10):1 and stir evenly to obtain a mixed solution. Spin the mixed solution onto the surface of the substrate to cover the patterned gold electrode, the spin coating speed is 1000rpm~4000rpm, and then place it on a heating table at 80℃~120℃ for drying, and the heating time is 5min~30min to obtain a polypropylene carbonate-polyvinyl alcohol mixed film.

[0088] (4) Controlling the temperature of the polypropylene carbonate-polyvinyl alcohol mixed film to 25°C-50°C, removing the substrate to obtain a mixed film-patterned gold electrode composite film, and attaching the composite film to a target substrate, with the patterned gold electrode side of the composite film facing the target substrate. In this embodiment, the target substrate is a silicon wafer.

[0089] (5) The target substrate is heated at a temperature of 50°C to 150°C to promote further bonding between the patterned gold electrode and the target substrate. After the target substrate is cooled to room temperature, the mixed film is cleaned with acetone or chloroform, and then the target substrate is blown dry with nitrogen to complete the transfer of the patterned gold electrode.

[0090] Referring to Figure 3, it can be seen that the patterned gold electrode transferred to the target substrate has high integrity and the electrode area can reach 9 cm 2 , this method can realize the transfer of patterned electrodes over a larger area.

[0091] Example 2

[0092] A method for transferring a patterned silver electrode, the specific steps are as follows:

[0093] In this embodiment, the transfer method of the patterned silver electrode is basically the same as the transfer method of the patterned gold electrode in Example 1, the difference being that the vapor-deposited gold electrode in step (2) is replaced with a vapor-deposited silver electrode, the mass ratio of the polypropylene carbonate solution to the polyvinyl alcohol solution in step (3) is 9:1, and the target substrate is an irregular curved surface.

[0094] 4 , it can be seen from the scanning electron microscope image that the transfer method of the present application can also achieve the transfer of patterned electrodes to irregular curved surfaces.

[0095] Example 3

[0096] A method for transferring a patterned polymer electrode, the specific steps are as follows:

[0097] (1) The silicon substrate is ultrasonically cleaned with deionized water, isopropanol, and acetone in sequence, and the cleaned silicon substrate is dried. The surface of the silicon substrate is cleaned by plasma to hydroxylate the surface, and the surface energy of the substrate is adjusted by liquid phase method. 10μL~100μL octadecyltrichlorosilane is dissolved in 50mL~250mL of n-heptane solution, and ultrasonicated for 1min~5min to make it evenly dispersed. The substrate is immersed in the solution for 1min~30min, and then the substrate is immersed in chloroform solution to clean it, and blown dry with nitrogen. The residual solvent is then dried on a heating table at 100℃~150℃ to obtain a monolayer modified substrate.

[0098] (2) Spin-coat the surface of the substrate obtained in step (1) with a conductive polymer. The conductive polymer used in this embodiment is PEDOT:PSS (Clevios PH1000). To improve its conductivity, 6% ethylene glycol is doped into the PEDOT:PSS aqueous solution, and 0.01%~0.5% fluorocarbon nonionic surfactant is introduced to adjust the wettability between the PEDOT:PSS aqueous solution and the substrate. The spin-coating speed is 1000rpm~6000rpm, and the spin-coating time is 40s~60s. After spin-coating, heat and anneal the substrate at 100℃~150℃, and the annealing time is 1min~30min. After the substrate temperature drops to room temperature, soak it in a nitric acid solution to remove excess PSS in PEDOT:PSS, thereby further improving the conductivity of the film. The nitric acid soaking time is 1min~30min. After taking out the substrate, wash the substrate with deionized water, and then blow dry it with nitrogen to obtain a polymer electrode film.

[0099] (3) Since the conductive polymer prepared in step (2) is an acidic material and is difficult to be compatible with the alkaline developer in the photolithography process, a metal film is deposited on the surface of the conductive polymer to protect the conductive properties of PEDOT:PSS. The metal film can be silver with a thickness of 20nm~40nm. Then, photolithography is performed on the surface of the silver film. The photolithography process is basically the same as step (2) in Example 1. A patterned photoresist is obtained on the surface of the silver film. The silver film not covered by the photoresist is removed by wet etching. The PEDOT:PSS not covered by the silver film is removed by dry etching. Finally, the silver film and photoresist remaining on the surface of the PEDOT:PSS are removed to obtain a patterned PEDOT:PSS electrode.

[0100] (4) The patterned polymer electrode transfer method is basically the same as steps (3) to (5) in Example 1.

[0101] 5 , it can be seen that the thin film material transfer method of the present application is also applicable to the transfer of polymer electrodes, and can achieve the transfer of polymer electrodes to a flexible substrate.

[0102] Example 4

[0103] A method for transferring a silver nanowire grid, the specific steps are as follows:

[0104] (1) The pretreatment method of the substrate is the same as step 1 in Example 1. The surface of the treated substrate is spin-coated with a silver nanowire aqueous dispersion to prepare a silver nanowire mesh film. The silver nanowire aqueous dispersion contains 0.01% to 0.5% by mass of a fluorocarbon nonionic surfactant for adjusting the wettability between the aqueous dispersion and the substrate. After spin coating, the substrate is heated and annealed at 120° C. to obtain a silver nanowire mesh film.

[0105] (2) Spin-coat the silver nanowire mesh film obtained in step (1) with a photoresist (model AZ 5200) at a speed of 3000 rpm to 6000 rpm for 40 s to 60 s, and then heat to solidify the film at 100°C to 120°C for 60 s to 600 s. Place the photoresist under a photolithography mask for UV exposure, and then place the substrate in a developer (AZ 400K: deionized water = 1:4) for 60 s to 200 s. After taking out the substrate, wash the substrate with deionized water and blow dry with nitrogen.

[0106] (3) Wet-etch the silver nanowire grid not covered by the photoresist. The etching solution is a mixed solution of KI, I2 and water. The etching time is 5s~300s. The substrate is then cleaned with deionized water, dried with nitrogen, and the residual photoresist is cleaned with acetone to obtain a patterned silver nanowire grid electrode.

[0107] (4) The method for transferring the patterned silver nanowire grid electrode is basically the same as steps (3) to (5) in Example 1, and the patterned silver nanowire grid electrode is transferred to the irregular bionic skin surface.

[0108] 6 , it can be seen that the thin film material transfer method of the present application is also applicable to the transfer of silver nanowire grids, and can achieve the transfer of silver nanowire grids to the surface of irregular bionic skin.

[0109] Example 5

[0110] The field effect transistor is prepared based on the thin film material transfer method in this application, referring to FIG. 7 , and the specific steps are as follows:

[0111] (1) Repeat steps (1) and (2) in Example 1 to obtain a patterned gold electrode on the substrate.

[0112] (2) Spin-coat polydimethylsiloxane (PDMS) on a glass substrate, with a mass ratio of PDMS mother liquor to cross-linking agent of 10:1, a spin-coating speed of 1000 rpm~6000 rpm, a curing temperature of 70°C~120°C, and a curing time of 3 min~30 min; then, spin-coat on the PDMS surface to prepare a polypropylene carbonate-polyvinyl alcohol mixed film, with a mass ratio of polypropylene carbonate to polyvinyl alcohol of 1:1, and a spin-coating speed of 3500 rpm. Then, place the glass substrate on a heating table at 100°C~120°C for drying, and the heating time is 5 min.

[0113] (3) Transfer the polypropylene carbonate-polyvinyl alcohol mixed film to the surface of the patterned gold electrode, and the contact temperature between the polypropylene carbonate-polyvinyl alcohol mixed film and the patterned gold electrode is 50°C to 90°C. Maintain the polypropylene carbonate-polyvinyl alcohol mixed film and the patterned gold electrode in contact for 2 min to 15 min until the temperature drops to 20°C to 25°C.

[0114] (4) Lift the glass substrate and PDMS as a whole. Connect the glass substrate to the mechanical cantilever. Refer to the common two-dimensional material directional transfer platform. Slowly lift the mechanical cantilever to transfer the patterned gold electrode to the surface of the polypropylene carbonate-polyvinyl alcohol mixed film.

[0115] (5) Align the patterned gold electrode on the polypropylene carbonate-polyvinyl alcohol mixed film to the target substrate and bond it. The alignment process is carried out under the assistance of a microscope. The bonding temperature with the target substrate is 90°C to 120°C. The mechanical cantilever connected to the glass substrate and PDMS is slowly raised to separate the polypropylene carbonate-polyvinyl alcohol mixed film from the PDMS, and then a patterned gold electrode is obtained on the target substrate. In this embodiment, the target substrate is a field effect transistor without a source electrode and a drain electrode. The transferred patterned gold electrode is the source electrode and the drain electrode of the field effect transistor. The polypropylene carbonate-polyvinyl alcohol mixed film attached to the patterned gold electrode can be removed by soaking in acetone and isopropanol for 5 minutes to 15 minutes. The cleaning process is carried out at room temperature.

[0116] Referring to (a) and (b) in FIG8 , this embodiment demonstrates the feasibility of applying the thin film material transfer method of the present application in preparing specific devices. The field effect transistor prepared in this embodiment is a bottom gate top contact structure device. Referring to (c) to (f) in FIG8 , the performance of the field effect transistor prepared in this embodiment is compared with that of the field effect transistor of the traditional thermal evaporation electrode. It can be seen that the mobility of the field effect transistor prepared by electrode transfer in this embodiment can reach 96 cm -2 v -1 s -1 , the on / off ratio is 10 8 The mobility of the field effect transistor of the conventional thermal evaporation electrode is 2.5 cm -2 v -1 s -1 , the on / off ratio is 10 5 The performance of the device prepared based on the electrode transfer method of this embodiment is significantly improved.

[0117] Example 6

[0118] The preparation of a flexible field effect transistor based on the thin film material transfer method in this application is carried out in the following specific steps:

[0119] The steps in Example 1 and Example 3 are repeated to prepare a patterned gold electrode as the gate electrode of the flexible field effect transistor, and a patterned polymer electrode as the source electrode and drain electrode of the flexible field effect transistor. Steps (3) to (5) in Example 5 are repeated to achieve electrode transfer, prepare a complete electrode structure in the flexible field effect transistor, and prepare a flexible field effect transistor by combining with a semiconductor material.

[0120] 9, the flexible field effect transistor prepared in this embodiment is a bottom-gate bottom-contact structure device, and its mobility can reach 26.9cm -2 v -1 s -1 , the on / off ratio is 10 8It can be seen that the transfer method of the present application is also applicable to the preparation of complex flexible device structures.

[0121] Example 7

[0122] Based on the thin film material transfer method in this application, large-area electrode transfer is performed to prepare a field effect transistor array. The specific steps are as follows:

[0123] Repeat steps (1) to (5) in Example 1 to transfer the large-area patterned gold electrode to the semiconductor surface. The semiconductor material is a large-area molybdenum disulfide film grown on the surface of silicon dioxide. The silicon dioxide serves as both a growth substrate and an insulating layer of the device.

[0124] Referring to FIG. 10 , the electrical performance of the devices of the large-area field effect transistor array was tested. 81 devices in the array were taken for electrical testing, and the average mobility was up to 58 cm -2 v -1 s -1 , the on / off ratio can reach 10 7 It can be seen that the transfer method of the present application is also applicable to large-area highly integrated devices.

[0125] Comparative Example 1

[0126] A method for transferring a patterned gold electrode based on a polypropylene carbonate (PCC) adhesive film, the specific steps are as follows:

[0127] (1) Repeat steps (1) and (2) in Example 1 to obtain a patterned gold electrode on the substrate.

[0128] (2) Spin coating a polypropylene carbonate solution on the surface of the patterned gold electrode to prepare an adhesive film. The solvent of the polypropylene carbonate solution is anisole. The mass concentration of polypropylene carbonate is 10% to 20%. The spin coating speed is 1000 rpm to 4000 rpm. After spin coating, the substrate is placed on a heating table at 80°C to 120°C for drying. The heating time is 5 min to 30 min.

[0129] (3) Controlling the temperature of the polypropylene carbonate adhesive film to 20° C. to 50° C., removing the substrate to obtain an adhesive film-patterned gold electrode composite film, and attaching the composite film to a target substrate, with the patterned gold electrode side of the composite film facing the target substrate. In this embodiment, the target substrate is a silicon wafer.

[0130] (4) The target substrate is heated at a temperature of 50°C to 150°C to promote further bonding between the patterned gold electrode and the target substrate. After the target substrate is cooled to room temperature, the mixed film is cleaned with acetone or chloroform, and then the target substrate is blown dry with nitrogen to complete the transfer of the patterned gold electrode.

[0131] Comparative Example 2

[0132] A method for transferring a patterned gold electrode based on a polyvinyl alcohol (PVA) adhesive film, the specific steps are as follows:

[0133] (1) Repeat steps (1) and (2) in Example 1 to obtain a patterned gold electrode on the substrate.

[0134] (2) Spin coating a polyvinyl alcohol solution on the surface of the patterned gold 2 electrode to prepare an adhesive film. The solvent of the polyvinyl alcohol solution is deionized water. The mass concentration of polyvinyl alcohol is 5% to 8%. The spin coating speed is 1000 rpm to 4000 rpm. After spin coating, the substrate is placed on a heating table at 80°C to 120°C for drying. The heating time is 5 min to 30 min.

[0135] (3) Controlling the temperature of the polypropylene carbonate adhesive film to 25° C. to 50° C., removing the substrate to obtain an adhesive film-patterned gold electrode composite film, and attaching the composite film to a target substrate, with the patterned gold electrode side of the composite film facing the target substrate. In this embodiment, the target substrate is a silicon wafer.

[0136] (4) The target substrate is heated at a temperature of 70°C to 150°C to promote further bonding between the patterned gold electrode and the target substrate. After the target substrate is cooled to room temperature, the mixed film is cleaned with acetone or chloroform, and then the target substrate is blown dry with nitrogen to complete the transfer of the patterned gold electrode.

[0137] Referring to Figure 11, comparing the optical microscope images of the patterned gold electrodes after transfer in Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that due to the excessive fluidity of polypropylene carbonate, the patterned gold electrode transferred based on the polypropylene carbonate (PCC) adhesive film is prone to wrinkles. In the gold electrode transferred based on the polyvinyl alcohol (PVA) adhesive film, it is difficult to ensure the integrity of the patterned electrode due to the lack of fluidity and adhesion of polyvinyl alcohol. The transfer of patterned gold electrodes based on polypropylene carbonate-polyvinyl alcohol mixed films can obtain a transfer patterned gold electrode with good flatness and completeness. Referring to Figure 12, the glass transition temperatures of three materials, polypropylene carbonate, polypropylene carbonate-polyvinyl alcohol mixed film and polyvinyl alcohol, were obtained by differential scanning calorimetry testing. It can be seen that the glass transition temperature of the polypropylene carbonate-polyvinyl alcohol mixed film in Example 1 is 35°C, which is between the glass transition temperatures of polypropylene carbonate and polyvinyl alcohol.

[0138] In summary, through the results of Examples 1 to 7, and the comparison between Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the glass transition temperature of polypropylene carbonate is low, and the fluidity is too strong, which easily causes the electrode to wrinkle and move during the transfer process, resulting in poor accuracy of electrode transfer. Polyvinyl alcohol has almost no fluidity and poor adhesion, making it difficult to ensure the integrity of the transfer electrode. In the present application, the polypropylene carbonate-polyvinyl alcohol mixed film has both a low glass transition temperature and moderate fluidity, and the adhesive film also has good mechanical strength and strong surface viscosity in an amorphous state, which can achieve electrode transfer with high integrity and high accuracy. At the same time, according to the results of Examples 1 to 7, it can be seen that the transfer method of the present application can be applied to a variety of thin film materials such as transfer metal electrodes, polymer films, metal grids, and can also be applied to the transfer of patterned electrodes on irregular surfaces. Further, the transfer method can also be applied to the actual preparation of various devices, including small area, flexible and large area array devices, and can achieve better device performance. The transfer method of the present application can realize the transfer of patterned electrodes with high precision, and also has the advantages of high repeatability, high operability and wide application range.

[0139] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0140] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.

Claims

1. A composition, characterized in that The composition comprises the following components in parts by weight: 1 to 20 parts of polypropylene carbonate and 1 to 2 parts of polyvinyl alcohol.

2. The composition according to claim 1, characterized in that The glass transition temperature of the composition is 35°C to 45°C.

3. A method for transferring a thin film material, characterized in that: include: forming a thin film material on a surface of a substrate; forming an adhesive film on the film material, wherein the adhesive film comprises the composition according to any one of claims 1 to 2, so that the adhesive film covers the film material to obtain a composite film comprising the film material and the adhesive film; Separating the composite film from the substrate, and attaching the composite film to a target substrate so that the thin film material of the composite film is in contact with the target substrate; The adhesive film is removed.

4. The thin film material transfer method according to claim 3, characterized in that: During the separation of the composite film from the substrate, the temperature of the adhesive film is controlled to be 25° C. to 50° C.

5. The thin film material transfer method according to claim 3, characterized in that: Laminating the composite film to a target substrate comprises: Heating causes the composite film to conform to the target substrate.

6. The thin film material transfer method according to claim 5, characterized in that: During the heating process to make the composite film adhere to the target substrate, the heating temperature is controlled to be 50° C. to 150° C.

7. The thin film material transfer method according to any one of claims 3 to 6, characterized in that: Removing the adhesive film comprises the following steps: The adhesive film is cleaned using one or more of acetone, chloroform, ethanol and isopropyl alcohol.

8. The thin film material transfer method according to any one of claims 3 to 6, characterized in that: The steps of forming a thin film material on the surface of a substrate include: reducing the surface energy of the substrate; The thin film material is prepared on the surface of the substrate after the surface energy is reduced.

9. The thin film material transfer method according to any one of claims 3 to 6, characterized in that: Forming an adhesive film on the thin film material comprises the following steps: Disposing a mixed solution including the polypropylene carbonate and the polyvinyl alcohol; The mixed solution is transferred onto the surface of the thin film material and dried.

10. The thin film material transfer method according to any one of claims 3 to 6, characterized in that: The thin film material includes one or more of a metal electrode, a polymer electrode, a metal grid, and a two-dimensional material; And / or, the material of the substrate includes at least one of glass, quartz, silicon wafer, ceramic, metal and plastic; And / or, the material of the target substrate includes at least one of glass, quartz, silicon wafer, ceramic, metal and plastic.

Citation Information

Patent Citations

  • Poly-methyl ethylene carbonate composition and preparation method thereof

    CN104371296A

  • Controllable flexible transfer method of two-dimensional materials

    CN104960286A

  • Method for transferring metal electrode to two-dimensional material

    CN114203541A

  • Non-homogeneous Young modulus matrix structure-based skin-like stretchable transparent electrode and preparation method and application thereof

    CN114694880A

  • Transfer method of metal electrode

    CN116313762A